2007
DOI: 10.1002/ijc.22951
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity as a prognostic factor in melanoma patients treated with adjuvant low‐dose interferon alpha

Abstract: Interferon alpha is used for the adjuvant treatment of malignant melanoma at different dosages (high-, intermediate-, low-dose therapy). Only a minority of patients might benefit from this therapy, and markers to identify such patients are missing. A recent study suggested that melanoma patients developing autoantibodies or clinical manifestations of autoimmunity during adjuvant highdose interferon alpha treatment had a significant survival benefit. We retrospectively reviewed 134 melanoma patients from our in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 26 publications
3
42
0
1
Order By: Relevance
“…Landmark analyses at 3 and 12 months showed a persistently strong association between autoimmune manifestations and RFS and OS (all P < 0.001). Analyzing the effects of autoimmunity in patients treated with low-dose interferon (LDI), Satzger et al [27] showed that the occurrence of autoimmune thyroid disease in 20 out of 134 patients (14.9%) correlated with a significantly better RFS (P ¼ 0.048) and a trend towards improved OS (P ¼ 0.065). The results of abovementioned trials appeared promising; however, since both studies analyzed the effects of autoimmunity on outcome in patients all receiving IFN treatment, the conclusion that autoimmunity could serve as a predictive marker for treatment response could not be drawn.…”
Section: Ifnamentioning
confidence: 98%
See 1 more Smart Citation
“…Landmark analyses at 3 and 12 months showed a persistently strong association between autoimmune manifestations and RFS and OS (all P < 0.001). Analyzing the effects of autoimmunity in patients treated with low-dose interferon (LDI), Satzger et al [27] showed that the occurrence of autoimmune thyroid disease in 20 out of 134 patients (14.9%) correlated with a significantly better RFS (P ¼ 0.048) and a trend towards improved OS (P ¼ 0.065). The results of abovementioned trials appeared promising; however, since both studies analyzed the effects of autoimmunity on outcome in patients all receiving IFN treatment, the conclusion that autoimmunity could serve as a predictive marker for treatment response could not be drawn.…”
Section: Ifnamentioning
confidence: 98%
“…Satzger et al [27] did not use any statistical tests to correct for guarantee-time bias and therefore the observation that autoimmunity is beneficial in patients treated with LDI is difficult to interpret. The other abovementioned studies performed landmark analyses and time-dependent Cox model analyses to correct for guarantee-time bias.…”
Section: Ifnamentioning
confidence: 98%
“…In a larger study about side effects of IFN treatment in hepatitis C, the rate of newly diagnosed RA after IFN start was 0.3% (2 of 677 patients) [10] while the prevalence of RA in the general population is 8/1000 [13]. This is in marked contrast to the frequent appearance of autoimmune thyroid antibodies under IFN treatment (26% according to the study by Gogas and coworkers [14]) and the high rate of clinical onset of autoimmune thyroid disease (15% according to the study by Satzger and coworkers [15]). …”
Section: To the Editormentioning
confidence: 99%
“…In the apparently unlikely event that RA is induced or exacerbated by IFN there is a good chance to control the disease by antirheumatic substances, although inhibitors of TNF are banned for use in patients with malignancies. In this context it is noteworthy that in melanoma the induction of exacerbation of RA under adjuvant IFN therapy may present a positive sign because the appearance of autoantibodies or clinical manifestations of autoimmunity during treatment with IFNa has been shown to be of significant improvement in PFS and OS [14,15].…”
Section: To the Editormentioning
confidence: 99%
“…For example, patients receiving type I IFN for treatment of malignancy show a significant increase in autoimmune thyroid disease [9]. In contrast, treatment of NOD mice with complete Freund adjuvant prevents the development of insulitis and autoimmune diabetes [10].…”
mentioning
confidence: 98%